Mathematical modeling of influence of the thermal power plant with considering the meteorological condition at the reservoir-cooler (Journal of Mathematics Mechanics and Computer Science, 2012)
This paper presents the mathematical model of the thermal power plant in cooling reservoir under different meteorological conditions, which is solved by Navier - Stokes equations and temperature equation for an incompressible fluid in a stratified medium. Numerical method based on projection method which is approximated by finite-difference method.
Keywords: thermal power plant; large eddy simulation; stratified medium; Navier-Stokes equation